Collective rights in a modernizing North – on institutionalizing Sámi and local rights to land and water in northern Norway. Issue 2 (1st July 2008) - Sandberg, Audun
The struggle by indigenous groups to have their rights acknowledged does not only take place through the action arenas of national political and constitutional processes, but also through active work through international bodies. Thus indigenous rights will often become arguments for institutional and constitutional changes in the modern world. The way such changes take place is nowadays more often through the incorporation of various forms of treaties and international charters into national legislation rather than direct negotiations between sovereign states and indigenous "tribes", "clans" or ethnic minority groups. However, when it comes to acknowledging the rights of ownership and possession of the peoples concerned over the lands which they traditionally occupy, these seem to be among the most difficult constitutional processes modern states can undertake. Thus they not only take much longer time than the granting of civil and political rights, but they also involve complex analytical exercises in order to understand the processes connected to the settling of indigenous land claims. This article analyses one such process in a nested and multi-tier system with parallel initiatives for institutional change.